Peran Self-esteem terhadap Peer Attachment pada Remaja dengan Orang Tua Bercerai di Kota Bandung - Yulita Anggelia; Jacqueline Tjandraningtyas; Yuspendi Yuspendi (Humanitas (Jurnal Psikologi), 2023)
Divorce is a significant event in the growth of a family. When divorce occurs, it not only affects the parents but also has an impact on the children. The occurrence of divorce negatively affects the development of children, particularly during adolescence. Furthermore, experiencing parental divorce leads adolescents to question their self-worth, resulting in the formation of low self-esteem, which in turn disrupts the development of peer attachment with their peers, as adolescents perceive themselves in a diminished light. Therefore, the aim of this study is to examine the influence of self-esteem on peer attachment. The subjects of this study are adolescents (aged 10-18 years) with divorced parents in Bandung City. The research method employed is quantitative. In this study, the researcher utilized the Inventory of Parent and Peer Attachment (Armsden & Greenberg, 1987) and the Self-esteem scale (Rosenberg, 1965), which were translated into Indonesian. IPPA consists of 25 items measuring peer attachment, with each scale comprising three aspects: trust, communication, and alienation. Meanwhile, the self-esteem scale consists of 10 items. The responses to both questionnaires (IPPA and self-esteem) will be analyzed using the linear regression method to determine the influence of self-esteem on peer attachment. The test results indicate a significance value of 0.030 (≤ 0.05). Thus, it can be concluded that self-esteem is related to peer attachment among adolescents with divorced parents in Bandung City.